WASTE BANK ESTABLISHMENT AS A FORM OF SUSTAINABLE ENTREPRENEURSHIP IN SERDANG WETAN VILLAGE - Putu Yani Pratiwi; Elissa Dwi Lestari; Purnamaningsih Purnamaningsih; Nosica Rizkalla; Arko Djajadi (Jurnal Sinergitas PKM & CSR, 2023)
According to data from the National Waste Management Information System 43.3% of the waste produced by the community comes from household waste. This figure makes households the largest source of waste generators. In South Tangerang city area, data from the South Tangerang Environmental Service shows that the waste generated by the people of South Tangerang city is 1000 tons every day. With the high volume of waste produced, household waste management has become an important thing to do so that waste is not just thrown away in the landfill. Serdang Wetan Village, which is one of the villages supported by Multimedia Nusantara University, currently does not have a waste bank, so the aim of the current Community Development Program is to establish a Waste Bank in Serdang Wetan Village. The program began with household waste management training to housewives in Serdang Wetan Village, then continued to form a WhatsApp group as a medium of information and communication. Every 2 weeks, the residents bring their clean household waste to the waste bank. This program has succeeded in raising public awareness about sorting waste, reducing waste entering the landfill, eliminating the habit of burning waste, and also providing additional income for the Serdang Wetan Village-Owned Enterprise (BumDes).